2017
DOI: 10.3233/ip-160012
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of open government data: A systematic literature review of types, conditions, effects and users

Abstract: This paper presents a comprehensive overview of the literature on the types, effects, conditions and user of Open Government Data (OGD). The review analyses 101 academic studies about OGD which discuss at least one of the four factors of OGD utilization: the different types of utilization, the effects of utilization, the key conditions, and the different users. Our analysis shows that the majority of studies focus on the OGD provisions while assuming, but not empirically testing, various forms of utilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(217 citation statements)
references
References 97 publications
4
203
0
10
Order By: Relevance
“…Furthermore, how effects of innovation barriers vary across different types of OGD users is poorly understood. In line with recent calls for studies on links between OGD user types and the effects of OGD use (Safarov et al, 2017), we argue that OGD-related research must seriously consider the heterogeneity among OGD users. Users are not homogenous in terms of for instance resources and knowledge.…”
Section: Introductionsupporting
confidence: 72%
“…Furthermore, how effects of innovation barriers vary across different types of OGD users is poorly understood. In line with recent calls for studies on links between OGD user types and the effects of OGD use (Safarov et al, 2017), we argue that OGD-related research must seriously consider the heterogeneity among OGD users. Users are not homogenous in terms of for instance resources and knowledge.…”
Section: Introductionsupporting
confidence: 72%
“…Institutional support in the Netherlands was found to be relatively weaker, although open data activities are coordinated at the ministerial level. A recent systematic literature review revealed that the open data activities in the Netherlands have been well researched by scholars (Safarov, Meijer, & Grimmelikhuijsen, 2017). In conclusion, centralization in OGD governance yields better results, as the experience in the UK shows.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, literature exists within the research community that explores different factors that influence the use of Open Data by citizens [13]. There have been many systematic literature reviews on the technical side of Open Data, and topics include the usage of open government data [14], Open Data initiatives [15], the publishing of Open Data [16], and classification, perspectives, benefits, and barriers of Open Data [17]. However, the possibilities and opportunities for Open Data usage in the domain of education have largely been overlooked.…”
Section: Literature Reviewmentioning
confidence: 99%